PERFORMANCE OF SPEED CHANGEABLE ASYMMETRIC PUMP CONTROLLED ASYMMETRIC HYDRAULIC CYLINDER - Kurbaniyazov. T.U; Sidikov. I.H; Kudenov. I.G; Najimatdinov. R.Q (International Engineering Journal For Research & Development, 2022)
Valves controlled cylinders are applied in many industries and mobile equipment due to their compact structure, high dynamic performance, and ease to drive more than one actuator by a single pump. Nevertheless, the energy-efficient is low, which is caused by the large throttling loss and the simultaneous actuation of the valves’ meter-in and meter-out control edges. These losses can be avoided by replacing the valve-controlled system with a pump-controlled system. In a typical pump-controlled asymmetric cylinder system, a complex and big flow circuit is necessary to compensate for the flow difference between the working ports of the cylinder.